2014
DOI: 10.1002/ajmg.a.36735
|View full text |Cite
|
Sign up to set email alerts
|

GALNS mutations in Indian patients with mucopolysaccharidosis IVA

Abstract: Mucopolysaccharidosis IV A (Morquio syndrome A, MPS IVA) is a lysosomal storage disease caused by the deficiency of N-acetylgalactosamine-6-sulfatase (GALNS). The mutation spectrum in this condition is yet to be determined in Indians. We aimed to analyze the mutations in the GALNS gene in Asian Indians with MPS IVA. All the exons and the adjacent intronic regions of the gene were amplified and sequenced in sixty-eight unrelated Indian families. We identified 136 mutant alleles comprising of 40 different mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 49 publications
9
40
1
Order By: Relevance
“…We hypothesize that the high rate of homozygous biallelic mutations (6/9; 67%) in the absence of consanguinity is due to the endogamous marriages within the same caste or community. Similar trends are also reported in other recessive disorders in India [Dalal et al, ; Bidchol et al, ].…”
Section: Discussionsupporting
confidence: 85%
“…We hypothesize that the high rate of homozygous biallelic mutations (6/9; 67%) in the absence of consanguinity is due to the endogamous marriages within the same caste or community. Similar trends are also reported in other recessive disorders in India [Dalal et al, ; Bidchol et al, ].…”
Section: Discussionsupporting
confidence: 85%
“…It is known that even in the absence of actual consanguinity, inbreeding can lead to homozygosity for recessive mutations and thereby result in disease in the offspring [Pemberton et al, ]. This is not an uncommon phenomenon in many regions of India where inbreeding within small communities in quite prevalent and similar findings have been documented in previous molecular genetic studies from India [Dalal et al, ; Bidchol et al, ].…”
Section: Discussionmentioning
confidence: 59%
“…Recent years have seen publication of genetic and mutation profiles for large case series of osteogenesis imperfecta, skeletal dysplasias, and lysosomal storage disorders. These studies have revealed the unique molecular profile of patients from the India with identification of many novel mutations not previously reported in other populations (Gorospe et al 2004;Pathak et al 2010;Sachdeva et al 2011Sachdeva et al , 2012Shukla et al 2011;Bashyam et al 2012;Dalal et al 2012;Mistri et al 2012;Bidchol et al 2014;Ankala et al 2015;Stephen et al 2015; A. Uttarilli, P. Ranganath, S.J.M. Nurul Jain, K.P.…”
Section: Academic Programs In Medical Geneticsmentioning
confidence: 93%
“…Use of SNP microarray to identify regions of homozygosity and candidate genes in these regions is a strategy which can be successfully used in the consanguineous families (Stephen et al 2015). Some conditions found to be relatively common have been Van Der Knaap disease with a founder mutation in the Agarwal community from north western India, calpainopahy, recessive forms of Osteogenesis imperfecta, Progressive pseudorheumatoid arthropthy of childhood and Handigodu disease from a specific community in South India (Gorospe et al 2004;Pathak et al 2010;Sachdeva et al 2011Sachdeva et al , 2012Shukla et al 2011;Bashyam et al 2012;Dalal et al 2012;Bidchol et al 2014;Ankala et al 2015). However, the available data on monogenic malformation syndromes and metabolic disorders from India though extensive, represents only tip of the iceberg as a large population still does not have access to the clinical genetics services due to cost and limited number of genetic centers.…”
Section: Spectrum Of Genetic Disordersmentioning
confidence: 99%